Tuesday
March 28, 2017

Post a New Question

Posted by on .

3n+40=-6(-2n+1)+1

  • Algebra 1 - ,

    3n+40=-6(-2n+1)+1

    3n + 40 = 12n - 6 + 1

    40 + 6 - 1 = 12n - 3n

    45 = 9n

    45/9 = n

    ? = n

  • Algebra 1 - ,

    5. And wouldn't it be -12n?

  • Algebra 1 - ,

    No. Multiplying 2 negatives produces a positive.

    -6 * -2n = 12n

  • Algebra 1 - ,

    oh wait never mind. I see my mistake now. Thanks for the help.

  • Algebra 1 - ,

    You're welcome.

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question